VAGINITIS: RECENT FORMULATION APPROACHES OF ANTI-INFECTIOUS DRUGS - R.ARUN KARTHICK; D.RAMYA DEVI; B.N.VEDHA HARI (International Journal of Pharma and Bio Sciences, 2014)
Vaginitis is mostly caused by Trichomonas vaginalis leading to mild to severe infections in the vaginal mucosa. The treatment for this disease can be initiated with the help of antimicrobial and antifungal agents in various dosage forms. Novel dosage forms have gained prior significance in recent formulation researches due to their inevitable controlled drug release mechanism and site specific applications. These systems include nanoparticles, micro particles, hydrogel systems, mucoadhesive systems, In-situ gels, etc. The physicochemical and biopharmaceutical parameters of the drug greatly influence the selection of the dosage form design. The attempt of this review is to enlighten the various novel approaches adopted for the design of antimicrobial and antifungal agents, such as Secnidazole, Fluconazole, Metronidazole, etc., with special emphasis on the treatment of vaginitis. Development of novel dosage forms of these antimicrobial agents would be a suitable way to achieve better therapeutic result against vaginitis.